STUDY OF THE EFFECT OF SEDIMENTATION ON CAPACITY AND CHANGES IN MORPHOLOGY OF THE TONDANO RIVER, MANADO CITY - Taufiq Makmur Zainuddin, M.
Sedimentation is a problem that always arises in several rivers in Indonesia, especially in the Tondano River, Manado City, and North Sulawesi Province. The Tondano River is one of the major rivers that cross the City of Manado, significantly contributing to the impact of flooding. The river is also affected by the tides. This research was conducted to analyze sediment transport and changes in river bed elevation that occurred within 1, 6, and 10 years using daily discharge due to sedimentation (scenario 1). As well as analyzing changes in the height of the riverbed during flood conditions during the Q2, Q5, and Q25 return periods (scenario 2). Sedimentation analysis was carried out using the HEC-RAS 6.1 application with the Meyer-Peter Muller method. The study location is in an urban area 7.2 km from the estuary. The topography data used is the 2016 topography for simulating sediment within six years, as well as calibration with 2022 topography and verification with current field conditions. The simulation results show that the Tondano River has experienced a significant change in river bed elevation. In 1 year, there is a sediment transport of 37,765.56 m3, a period of 6 years of sediment transport of 83,087.49 m3 with an average sedimentation thickness of 0.891 m and an estimate of 0.130 to 0.140 m per year if this condition is verified by the cross-section of the river Tondano is currently experiencing siltation and causing a reduction in the river's capacity to carry flood discharge. The change in river bed elevation also causes an increase in the average water level as high as 1.00 to.d. 1.20m. Meanwhile, 190,301.09 m3 of sediment transport was obtained in the ten years. Then for scenario two, an analysis of changes in the river bed was carried out during flood conditions Q5 with the result that erosion tends to occur in the upstream and middle parts of the river around 3 – 8 cm. While sedimentation occurred during the flood period of 2,738.72 m3. In Q25 flood conditions, erosion tends to appear in the upper and middle parts of the river around 5 – 12 cm. At the same time, sedimentation occurred during the flood period of 3,238.43 m